Tree Planting before Merriage in Village Regulation No. 2 of 2009 in Bone-Bone Village, Enrekang Regency According to Maslahah - Khairiah, Nahdiatul; Salam, Abdul; Jumadil, Jumadil; Kappaja, Ismail; BN, Andi Muh. Taqiyuddin (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2024)
This research was conducted to know (1) the implementation of regulation no. 2 of 2009 Article 3 Bone-Bone Village and (2) the perspective of benefits for the implementation of Bone-Bone Village regulations No. 2 of 2009 Article 5. This research is field research using qualitative methods. The approach used in this study is an empirical juridical approach, with data collection techniques through observation, interviews, and document review. primary and secondary primary data obtained by conducting interviews with village government, religious leaders, and communities involved secondary data from documents related to data analysis techniques in this study starting from the data collected and then analyzed, then classifying the data that has been collected then the data is concluded.The results of this study indicate that (1) Implementation of Regulation No. 2 of 2009 Article 5 Bone-Bone Village, there are two, namely the first introduction to Regulation No. 2 of 2009 Article 5 which introduces the regulation using socialization. Then the second is the stage of implementing regulation No.2 of 2009 Article 5, namely registration, then planting trees and reporting; (2) Rules for planting trees No. 2 of 2009 Article 5 This regulation aims for the benefit and welfare of the community. From the perspective of this benefit, it is maslahat mursalah. Maslahat mursalah is something that brings benefits (profits) and keeps harm (damage) away.